Current aspects of studying accommodation disorders in the context of autonomic nervous regulation - A. Zh. Fursova; M. K. Artykova (Российский офтальмологический журнал, 2025)
Habitual excessive accommodation tension (HEAT) in children is associated with ciliary muscle spasm, reduced distance visual acuity, and asthenopic symptoms. Studies highlight the role of the autonomic nervous system (ANS) in accommodation regulation, while an imbalance between sympathetic and parasympathetic activity, triggered by stress and visual load, may contribute to the development of HEAT. Modern diagnostic methods, such as heart rate variability and pupillometry, enable the study of ANS influence on accommodation. Various correction approaches are considered, including pharmacological and physiotherapeutic methods, as well as restoring autonomic balance. Further research is needed to explore the impact of the ANS on accommodation in children.